Influência da mineralogia do solo e da microbiota associada à rizosfera de adubos verdes na fitorremediação do herbicida sulfentrazone - Santos, Esequiel (2017)
Several factors may interfere with phytoremediation performance of herbicides in soil, in particular mineralogy and microbial activity. The effect of mineralogy and rhizosphere on the phytoremediation of the herbicide sulfentrazone was evaluated in order to carry out research in soil conditions using Canavalia ensiformis and Crotalaria juncea species. In the first stage, the treatments were composed by a combination of three types of soils, with different textures, varying the mineralogy of clay fraction dominated by one type of mineral (kaolinite, hematite and gibbsite) and two doses of sulfentrazone (0 and 400 g ha-1), arranged in a 3 x 3 x 2 factorial scheme, in DBC, with three replications. For the bioassay, a bioindicator species of sulfentrazone residue was seeded in the soil, millet (Pennisetum glaucum). The results showed that the herbicide movement was higher in the kaolinite soil and herbicide retention was higher in the hemattic soil. Phytoremediation was more efficient in the preculture of C. ensiformis in the gibbsite, reducing by 28% the applied sulfentrazone load. There was no result for hematological soil. In the kaolinite soil, C. ensiformis reduced the total sulfentrazone mass by approximately 11% and C. juncea by 19%. In the second stage, it was also evaluated the rhizospheric microbial contribution of these same species in the phytoremediation of sulfentrazone. The treatments were composed by the combination of two rhizospheric soils (pork and crotalaria) and one non-rhizosphere with four levels of sulfentrazone herbicide (0, 200, 400 and 800 g ha-1), arranged in a 3 x 4 factorial scheme. Evolution of CO2, microbial biomass carbon (CBM), metabolic quotient (qCO2), biometric components and phytotoxicity in P. glaucum were evaluated in bioassay and soil liquid chromatography. The results indicated that the cultivation of phytoremediate species promoted an increase in microbial activity and it was verified that the profiles bacterial genotypes were formed according to the plant and soil characteristics (rhizospheric and non - rhizospheric), increasing knowledge about the associations between plants and microorganisms.